2013
DOI: 10.1523/jneurosci.5481-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Sympathetic Neuron Autonomous Role for Egr3-Mediated Gene Regulation in Dendrite Morphogenesis and Target Tissue Innervation

Abstract: Egr3 is a nerve growth factor (NGF)-induced transcriptional regulator that is essential for normal sympathetic nervous system development. Mice lacking Egr3 in the germline have sympathetic target tissue innervation abnormalities and physiologic sympathetic dysfunction similar to humans with dysautonomia. However, since Egr3 is widely expressed and has pleiotropic function, it has not been clear whether it has a role within sympathetic neurons and if so, what target genes it regulates to facilitate target tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 112 publications
(167 reference statements)
1
29
0
Order By: Relevance
“…Reverse transcriptase (RT)-PCR and qPCR were performed as previously (Albert et al, 2005;Quach et al, 2013) and are outlined in detail in supplementary methods (see supplementary material).…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse transcriptase (RT)-PCR and qPCR were performed as previously (Albert et al, 2005;Quach et al, 2013) and are outlined in detail in supplementary methods (see supplementary material).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…In vivo ganglion neuron counts and primary neuron culture and cell survival Neuron counts and primary neuron culture were performed as previously described (Quach et al, 2013). Primary neuron survival was performed as previously described and detailed as previously described (Eldredge et al, 2008).…”
Section: Immunohistochemistry and Western Blottingmentioning
confidence: 99%
“…1823 Additionally, EGR molecules are critically involved in stabilization of neuronal plasticity, neuron outgrowth and cytoskeletal regulation. 16,21,2325 Chronic stress mediates widespread adaptations to synaptic density and dendritic arbor. 26 Stress-induced impairment in structural and synaptic alterations as well as their molecular underpinnings have been extensively studied in limbic excitatory brain regions, 2628 but there is minimal information into these mechanisms in GABAergic neurons, including MSN subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The zinc finger-containing immediate early gene transcription factor Egr3 has a demonstrated role in axon growth (Eldredge et al, 2008; Quach et al, 2013). Interestingly, Egr3 null mice have degenerating muscle spindles, (Tourtellotte and Milbrandt, 1998) which fail to express NT-3, which results in type Ia afferents failing to reach their targets in the muscle spindle (Chen et al, 2002).…”
Section: Developmental Axon Growthmentioning
confidence: 99%
“…Egr3 is also required for proper innervation of salivary glands and heart where NGF and NT-3 expression persist in the absence of Egr3 suggesting that Egr3 regulates axon growth via neurotrophin-independent factors in these contexts. More recent studies have demonstrated a role for Egr3 in sympathetic neuron axon branching and dendritic morphology (Quach et al, 2013). …”
Section: Developmental Axon Growthmentioning
confidence: 99%